Epidemiology and Recurrence Rates of Clostridium difficile Infections in Germany: A Secondary Data Analysis. Issue 4 (December 2016) - Lübbert, Christoph; Zimmermann, Lisa; Borchert, Julia; Hörner, Bernd; Mutters, Reinier; Rodloff, Arne
Abstract Introduction Clostridium difficile infection (CDI) is the most common cause of health-care-associated infectious diarrhea. Recurrence rates are as high as 20–30% after standard treatment with metronidazole or vancomycin, and appear to be reduced for patients treated with fidaxomicin. According to the literature, the risk of CDI recurrence increases after the second relapse to 30–65%. Accurate data for Germany are not yet available. Methods Based on the research database of arvato health analytics (Munich, Germany), a secondary data analysis for the incidence, treatment characteristics and course of CDI was performed. The database included high granular accounting information of about 1.46 million medically insured patients covering the period 2006–2013, being representative for Germany. The analysis was based on new-onset CDI in 2012 in patients which either received outpatient antibiotic therapy for CDI or were hospitalized. Results The ICD-10 coded incidence of CDI in 2012 was 83 cases per 100, 000 population. Overall mortality rates within the follow-up period of 1 year were 13.5% in inpatients with primary diagnosis of CDI, compared to 24.3% in inpatients with secondary diagnosis of CDI (P < 0.001), and 7.1% in outpatients (P < 0.001). In the median, patients with secondary diagnosis of CDI remained significantly longer hospitalized (24 vs. 9 days, P < 0.001). First recurrence of CDI was observed in 18.2% of cases with index events. There was a significantly increased risk to suffer a second and third recurrence, reaching 28.4% (P < 0.001), and 30.2% (P = 0.017), respectively. Antibiotic therapy of CDI in outpatients was performed mainly with metronidazole (in 90.8% of index events, 60.0% of first recurrences, and 43.5% of second recurrences). Conclusion The reported incidence of CDI in Germany is higher than noted previously. The recurrence rates do increase with the number of relapses, but are lower than reported in the literature, despite dominance of metronidazole treatment in outpatients. Funding MSD Sharp & Dohme GmbH, Haar, Germany.